DETERMINAN INDEKS PEMBANGUNAN MANUSIA DI PROVINSI JAWA TIMUR: MODEL CROSSECTIONAL SPASIAL - Santoso, Edy; Jumiati, Aisah; Hadi Priyono, Teguh; Putomo Somaji, Rafael (UNIVERSITAS NUSANTARA PGRI KEDIRI, 2022)
The purpose of this study was to analyze the determinants of the human development index in East Java Province. Using the Human Development Index (HDI) data in 2020, spatial econometric models were used to identify the effect of GRDP, Population, Unemployment Rate and City Minimum Wage on HDI in East Java Province. The results of the competition on the three models show that the best model for estimating the HDI in East Java Province is the Spatian Error Model (SEM) compared to the Spatial Leg Model (SLM) and the Ordinary Least Square Model (OLS). The results of the Spatial Error Model Estimation show that GRDP and unemployment have a positive and significant impact on HDI in East Java Province during the study period. This means that GRDP and unemployment are able to encourage an increase in HDI in East Java Province. While the population variable has a negative and significant effect on the human development index in East Java Province. This means that the smaller the population will be able to encourage an increase in HDI in East Java Province. The UMK variable shows an insignificant effect, which means that the variable has not been able to influence the amount of HDI in East Java Province. The estimation results of the SEM model also show a positive and significant value of lamda, which can be interpreted that there is a spatial effect in the formation of HDI in East Java Province through error components.